2021
DOI: 10.1021/acs.jpcc.0c09057
|View full text |Cite
|
Sign up to set email alerts
|

Role of Methyl Acetate in Highly Reproducible Efficient CsPbI3 Perovskite Quantum Dot Solar Cells

Abstract: The best research-cell efficiency for quantum dot solar cells has boosted from 11.6 to 18.1% within 5 years due to the evolution of perovskite quantum dots (PQDs) that are being intensively developed along with the flourishing of perovskite thin-film photovoltaics. During the fabrication of PQD devices, as far as we know, methyl acetate (MeOAc) is an ineluctable solvent in ligand exchange for producing highly efficient solar cells. Nevertheless, the reproducibility for PQD solar cells using MeOAc treatment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 77 publications
1
44
0
Order By: Relevance
“…[ 29b ] However, the processing window of the MeOAc and FAI treatments is very narrow and the ability to remove the original ligand is limited. [ 29b,91,93 ]…”
Section: Scale‐up Of Pqd Solar Cellsmentioning
confidence: 99%
“…[ 29b ] However, the processing window of the MeOAc and FAI treatments is very narrow and the ability to remove the original ligand is limited. [ 29b,91,93 ]…”
Section: Scale‐up Of Pqd Solar Cellsmentioning
confidence: 99%
“…They demonstrated that the device undergoing three-cycle MeOAc treatment can achieve the highest PCE of 12.85% staying phase stability. [41] However, the pure solvent treatment brings about some shortcomings. First, the ligand exchanging rate and degree depend on the amount of adventitious water as well as the extent of ester hydrolyzation.…”
Section: Solid-state Ligand Exchanging For Pqdscsmentioning
confidence: 99%
“…To date, MAPbX 3 , FAPbX 3 , and CsPbX 3 QDs with high have been successfully synthesized as well as their hybridization. However, MA-based PQDs exhibit poor chemical stability due to their low Ligand engineering CsPbI 3 PQDs 10.8% - [28] FAPbI 3 PQDs 8.4% 226 h (continuous illumination) 99% of initial PCE [37] CsPbI 3 PQDs 11.9% - [38] CsPbI 3 PQDs 14.6% - [39] CsPbI 3 PQDs 11.2% 1 month (20% RH in air) 80% of initial PCE [24] CsPbBr 3 PQDs 4.2% - [40] CsPbI 3 PQDs 12.9% - [41] CsPbI 3 PQDs 14.1% -…”
Section: Performance Enhancement Of Pqdscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exchange chemistry is favorable for the mitigation of defect density, amelioration of film quality, improvement of light absorption, and acceleration of charge transport. Both ion exchange and ligand change can contribute to the advancement of perovskite QDs and QD‐based solar cells [27, 28] . The passivation engineering strategy can be achieved by ion passivation and ligand passivation [29, 30] .…”
Section: Introductionmentioning
confidence: 99%